Immunotyping of Human Immunodeficiency Virus Type 1 (HIV): an Approach to Immunologic Classification of HIV - Zolla-Pazner, Susan (American Society for Microbiology, 1999)
Because immunologic classification of human immunodeficiency virus type 1 (HIV) might be more relevant than genotypic classification for designing polyvalent vaccines, studies were undertaken to determine whether immunologically defined groups of HIV (“immunotypes”) could be identified. For these experiments, the V3 region of the 120-kDa envelope glycoprotein (gp120) was chosen for study. Although antibodies (Abs) to V3 may not play a major protective role in preventing HIV infection, identification of a limited number of immunologically defined structures in this extremely variable region would set a precedent supporting the hypothesis that, despite its diversity, the HIV family, like the V3 region, might be divisible into immunotypes. Consequently, the immunochemical reactivities of 1,176 combinations of human anti-V3 monoclonal Abs (MAbs) and V3 peptides, derived from viruses of several clades, were studied. Extensive cross-clade reactivity was observed. The patterns of reactivities of 21 MAbs with 50 peptides from clades A through H were then analyzed by a multivariate statistical technique. To test the validity of the mathematical approach, a cluster analysis of the 21 MAbs was performed. Five groups were identified, and these MAb clusters corresponded to classifications of these same MAbs based on the epitopes which they recognize. The concordance between the MAb clusters identified by mathematical analysis and by their specificities supports the validity of the mathematical approach. Therefore, the same mathematical technique was used to identify clusters within the 50 peptides. Seven groups of peptides, each containing peptides from more than one clade, were defined. Inspection of the amino acid sequences of the peptides in each of the mathematically defined peptide clusters revealed unique “signature sequences” that suggest structural motifs characteristic of each V3-based immunotype. The results suggest that cluster analysis of immunologic data can define immunotypes of HIV. These immunotypes are distinct from genotypic classifications. The methods described pave the way for identification of immunotypes defined by immunochemical and neutralization data generated with anti-HIV Env MAbs and intact, viable HIV virions.